The dynamic of decision-making: Effect of intertemporal choice on clothing products - Kylila, Amabel; Elgeka, Honey Wahyuni Sugiharto (HUMANITAS published by Universitas Ahmad Dahlan., 2024)
Individuals' emotional states (i.e., happy and sad emotions) might influence the intertemporal choice process, a decision of choosing between instant alternatives with small advantages or delayed alternatives with enormous benefits, when purchasing a product. This study tested the role of emotional states in individual intertemporal choices, especially when buying clothing products. 45 active students were involved as participants in this experimental study.' The results indicated that happy and sad emotions do not significantly differ in individuals' intertemporal choices, specifically in purchasing clothing products (ꭓ2 = 5.293, p > 0.05). This study also found that intertemporal choice was influenced by gender (F = 6.431, p < 0.05). This gender difference was significant (ꭓ2 = 4.099, p < 0.05), in which female participants had a higher average delayed gratification than male participants. Even though differences in income did not significantly impact the differences in intertemporal choice (ꭓ2 = 5.962, p > 0.05), individual income influenced intertemporal choice (F = 4.381, p < 0.05), in which participants with smaller incomes tended to choose cheaper clothing product. Moreover, the system of three thinking inhibited irrationality and made students more rational when making purchase decisions in accordance with their income or pocket money.